Lecanicillium sabanense sp. nov. (Cordycipitaceae) a new fungal entomopathogen of coccids - Chiriví-Salomón, Juan S; Danies, Giovanna; Restrepo, Silvia; Sanjuan, Tatiana (Phytotaxa, 2015)
A new species of Lecanicillium was found associated with the soft scale insect Pulvinaria caballeroramosae (Coccidae), an important pest of Ficus soatensis (Moraceae) in Bogotá, Colombia. Lecanicillium sabanense sp. nov. differs from similar Lecanicillium spp. mainly in the size of the conidia, in the vertical arrangement of phialides on the host, and in the tomentose mycelium that sparsely covers the cuticle of the host. Phylogenetic analyses using ITS, SSU, LSU, TEF, RPB1, and RPB2 also confirmed the distinctness of this new species. Fungal epizootics were found on female soft scale insects, which may have implications for biological control in the forestry program of the city. The ecology of the fungus as well as its potential use as a biological control agent are further discussed.